2016
DOI: 10.1007/s00248-016-0790-0
|View full text |Cite
|
Sign up to set email alerts
|

Rainforest Conversion to Rubber Plantation May Not Result in Lower Soil Diversity of Bacteria, Fungi, and Nematodes

Abstract: Large areas of rainforest in Asia have been converted to plantations, with uncertain effects on soil biodiversity. Using standard metagenetic methods, we compared the soil biota of bacteria, fungi, and nematodes at three rainforest sites in Malaysia with two rubber plantation sites with similar soils and geology. We predicted the following: (1) that the rubber sites would have a lower α- and β-diversity than the rainforest sites, due to the monospecific canopy cover and intensive management with herbicides, pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
58
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 65 publications
11
58
0
Order By: Relevance
“…The composition of the soil bacterial community in rubber plantations was similar to forest ecosystems (Li et al, 2014; Lin et al, 2014; Siles and Margesin, 2016), possibly because rubber plantations retain some common attributes of forest ecosystems after the forest is converted. Thus, a forest's conversion to a rubber tree plantation does not necessarily mean that the bacterial community's diversity will be reduced or lost (Kerfahi et al, 2016; Lan et al, 2017). In fact, previous work has shown that there were often no differences in the diversity of bacterial communities between agricultural soil and natural forest soil, with diversity of the soil bacterial community in the agricultural soil occasionally even higher than the natural forest soil (Jangid et al, 2008; Upchurch et al, 2008; Tripathi et al, 2012; Lee-Cruz et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The composition of the soil bacterial community in rubber plantations was similar to forest ecosystems (Li et al, 2014; Lin et al, 2014; Siles and Margesin, 2016), possibly because rubber plantations retain some common attributes of forest ecosystems after the forest is converted. Thus, a forest's conversion to a rubber tree plantation does not necessarily mean that the bacterial community's diversity will be reduced or lost (Kerfahi et al, 2016; Lan et al, 2017). In fact, previous work has shown that there were often no differences in the diversity of bacterial communities between agricultural soil and natural forest soil, with diversity of the soil bacterial community in the agricultural soil occasionally even higher than the natural forest soil (Jangid et al, 2008; Upchurch et al, 2008; Tripathi et al, 2012; Lee-Cruz et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…They determined that the soil microbial community structure and biomass of rubber tree plantations were different in different soil parent materials, and that the variation of soil microbial biomass with rubber tree age resulted from different soil parent materials, concluding that the main factors affecting microbial communities in soil were soil parent material and soil nutrients (Guo et al, 2013, 2015). In addition, using high-throughput sequencing, a few studies have examined the effects on bacterial diversity and composition after forests have been converted into rubber tree plantations (Kerfahi et al, 2016; Yang, 2016; Lan et al, 2017). Kerfahi and Lan revealed that the conversion of tropical forest to rubber tree plantations did not result in lower diversity of soil bacterial, determining that bacterial diversities in rubber tree plantations were higher than in tropical forests, and that soil nutrition was the most important factor affecting the soil bacterial community (Kerfahi et al, 2016; Lan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in bacterial alpha diversity following conversion to agriculture differs sharply with commonly reported decreases in the diversity of plants (Ibrahim et al, 2003), animals (Bierregaard, 2001; Brook, Sodhl, & Ng, 2003; Gardner et al, 2009) and fungi (Cai, Zhang, Yang, & Wang, 2018; Kerfahi, Tripathi, Dong, Go, & Adams, 2016; Lan et al, 2017; McGuire et al, 2015; Mueller et al, 2014). This difference may result from ecological differences between bacteria and eukaryotes; for example, bacterial diversity may respond to changes in soil chemical properties, rather than being directly affected by land use change.…”
Section: Discussionmentioning
confidence: 67%
“…Second, inclusion of other soil organisms such as fungi, nematodes and microarthropods will allow for a more complete understanding of how soil ecosystems are affected by land use change (as in Kerfahi et al . 2016).…”
Section: Discussionmentioning
confidence: 99%